Rural life and activities at Burren Burren Station and Collarenebri, New South Wales, 1951 - Reiss, Francis, 1927-2017. (1951)
Collection of photographs of Rex White owner of a sheep and cattle station at Burren Burren property in 1951, near Collarenebri. Includes daily rural activities of his wife Helen, sheep shearing, mustering sheep into yards, skinning sheep and wool pressing into bales. Also includes photographs of Collarenebri local shopping town.
Title devised by cataloguer based on information supplied by photographer.
Also available online
Purchased from Francis Reiss, 2008.
Keywords: Ranches -- New South Wales -- Collarenebri -- Photographs; Sheep ranchers -- New South Wales -- Collarenebri -- Photographs; Farm life -- New South Wales -- Collarenebri -- Photographs; Burren Burren Station (N.S.W.) -- Photographs; Collarenebri (N.S.W.) -- Photographs